Association Between Egg Consumption and Dementia Risk in the EPIC-Spain Dementia Cohort - Margara-Escudero, Hernando J.; Zamora-Ros, Raul; de Villasante, Izar; Crous-Bou, Marta; Chirlaque, María-Dolores; Amiano, Pilar; Mar, Javier; Barricarte, Aurelio; Ardanaz, Eva; Huerta, José María (Frontiers in Nutrition, 2022)
Background: Current evidence suggests that egg composition might have potential neuroprotective effects. Our aim was to determine the association between egg consumption and the risk of dementia in a Mediterranean population. Methods: This study was carried out in 3 centers from the European Prospective Investigation into Cancer and Nutrition (EPIC)-Spain Dementia Cohort, including 25,015 participants aged 30–70 years, recruited in 1992–1996 and followed-up for a mean of 21.5 years. A total of 774 incident dementia cases were diagnosed and validated, of which 518 were Alzheimer disease (AD). Data on egg consumption was estimated using a validated dietary history questionnaire at recruitment. Cox proportional hazards models, adjusted for confounders, were used in the analyses. Results: No association was observed between egg consumption and either total dementia (hazard ratio between extreme quartiles (HRQ4 vs Q1: 1.05; 95% CI 0.85–1.31; P-trend = 0.93)) or AD (HRQ4 vs. Q1 0.93; 95% CI 0.72 -1.21; P-trend = 0.50) risks. After dividing the population by Mediterranean diet (MD) adherence, a borderline inverse association was found between egg intake and both total dementia (HR:0.52; 95% CI 0.30-0.90; p-trend = 0.10) and AD (HR: 0.52; 95% CI 0.27-1.01; p-trend = 0.13) risks within participants with low adherence to MD. However, no association was observed in participants with medium and high adherence to MD. Conclusion: This prospective study suggests that egg consumption is associated with a reduced risk of dementia, and specifically of AD, in adult population with low adherence to MD; whereas it has no impact in subjects with moderate and high MD adherence.